1999
DOI: 10.1152/jappl.1999.87.4.1513
|View full text |Cite
|
Sign up to set email alerts
|

Validity of fan-beam dual-energy X-ray absorptiometry for measuring fat-free mass and leg muscle mass

Abstract: The aim of the study was to examine the accuracy of fan-beam dual-energy X-ray absorptiometry (DEXA) for measuring total body fat-free mass (FFM) and leg muscle mass (MM) in elderly persons. Participants were 60 men and women aged 70-79 yr and with a body mass index of 17.5-39.8 kg/m(2). FFM and MM at four leg regions were measured by using DEXA (Hologic 4500A, v8.21). A four-compartment body composition model (4C) and multislice computed tomography (CT) of the legs were used as the criterion methods for FFM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(167 citation statements)
references
References 12 publications
5
151
0
11
Order By: Relevance
“…The validity and reproducibility of the body composition data in the Health ABC Study may be found elsewhere (13,14). Quality assurance measures included the use of a body composition phantom for calibration and annual assessment for potential site differences or drift over time.…”
Section: Body Compositionmentioning
confidence: 99%
“…The validity and reproducibility of the body composition data in the Health ABC Study may be found elsewhere (13,14). Quality assurance measures included the use of a body composition phantom for calibration and annual assessment for potential site differences or drift over time.…”
Section: Body Compositionmentioning
confidence: 99%
“…Kim et al, fueron capaces de estimar la masa muscular total por medio del método DEXA (Kim et al, 2002(Kim et al, , 2004Shih et al, 2000;Levine et al, 2000;Visser et al, 1999), pero no consiguieron dividir este compartimiento por segmentos corporales. Por este motivo, el desarrollo del método antropométrico de fraccionamiento por regiones y validado por DEXA, permitiría realizar comparaciones específicas entre la manera en que se distribuyen los tejidos (Lohman & Chen, 2005), y su influencia en el rendimiento físico, como la masas grasa y muscular, de acuerdo a la actividad deportiva que realiza cada individuo, teniendo de este modo información de la distribución y desarrollo físico diferenciado, que el simple análisis de la totalidad de cada componente de la composición corporal, no es capaz de proporcionar.…”
Section: Introductionunclassified
“…Tanto a tomografia computadorizada como o modelo tetracompar timental foram utilizados como critério para validar a AXDE na mensuração da massa muscular e massa livre de gordura, respectivamente 7 . Foi encontrado que ambas variáveis, quando estimadas pela AXDE, são positivamente associadas e estatisticamente maiores do que os valores obtidos pelos métodos citados.…”
Section: Absortometria De Raio-x De Dupla Energiaunclassified
“…Entretanto, esta perda pode ocorrer de forma exagerada, caracterizando a osteoporose, que tem como conseqüência o aumento da fragilidade esquelética e do risco de fraturas Alguns instrumentos para detectar a perda da DMO foram desenvolvidos ao longo do tempo, e o mais utilizado ultimamente é a absortometria de raio-x de dupla energia (AXDE). Muitos estudos confirmam a validade e a precisão da AXDE tanto para medidas de DMO 3-5 quanto de adiposidade 6 e massa muscular/ massa magra 7 …”
Section: Introductionunclassified